Loss of adhesion/growth‐regulatory galectin‐9 from squamous cell epithelium in head and neck carcinomas. (31st May 2012) - Fík, Zdeněk; Valach, Jaroslav; Chovanec, Martin; Mazánek, Jiří; Kodet, Roman; Kodet, Ondřej; Tachezy, Ruth; Foltynová, Eva; André, Sabine; Kaltner, Herbert; Gabius, Hans‐Joachim; Smetana, Karel
<x xml:space="preserve">Abstract</x> J Oral Pathol Med (2013)42: 166–174 Galectins are potent effectors of cell adhesion and growth regulation. Their expression as comples network necessitates systematic study of each member of this family. Toward this aim, we here focus on the tandem‐repeat‐type galectin‐9. Its presence is monitored in normal squamous epithelium of the head and neck, the surgical margin, and four types of squamous cell carcinoma. Lectin presence was detected in cells of the basal layer of the epithelium. All galectin‐9‐negative epithelia showed aberrant positivity for keratins 14 and 19. The surgical margin presented either a normal pattern of galectin‐9 and keratin presence or a mosaic‐like presence/absence of galectin‐9 and aberrant expression of both keratins 14 and 19. All studied specimens of squamous cell carcinoma were negative for galectin‐9. When biotinylated galectin‐9, or its N‐terminal domain, was tested, no significant tissue reactivity for both probes was observed. Neuraminidase treatment generated reactivity to the N‐domain. In conclusion, galectin‐9 is expressed in the majority of samples of normal epithelium, along with regular presence of keratins 14 or 19. This lectin can represent a potential marker of normality in the cases of the studied squamous cell epithelia.